INDOOR AIR MICROBIOLOGICAL CONTAMINATION ASSESSMENT EDUCATION INSTITUTION - Sproģe, Kristīne; Tretjakova, Rasma (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The indoor environmental quality issue in the educational institution is updated in the paper. All people are exposed to indoor air microbial contamination exposure. As an educational institution for several years children spend up to 1/3 of each working day, it is very important to create a regulatory compliant, healthy and comfortable environment, which would not have any adverse impact on the state of health and labor.